Acute Traumatic Myelopathy: Rethinking Central Cord Syndrome. Issue 23 (1st December 2022) - Bulloch, Landon R.; Spector, Leo; Patel, Alpesh
Abstract : Central cord syndrome (CCS) is an incomplete spinal cord injury that consists of both sensory and motor changes of the upper and lower extremities. CCS most commonly occurs after trauma to the cervical spine leading to acute neurological changes. Despite being the most common incomplete spinal cord injury with the best outcomes, optimal treatment remains controversial. Although clinical practice has shifted from primarily conservative management to early surgical intervention, many questions remain unanswered and treatment remains varied. One of the most limiting aspects of CCS remains the diagnosis itself. CCS, by definition, is a syndrome with a very specific pattern of neurological deficits. In practice and in the literature, CCS has been used to describe a spectrum of neurological conditions and traumatic morphologies. Establishing clarity will allow for more accurate decision making by clinicians involved in the care of these injuries. The authors emphasize that a more precise term for the clinical condition in question is acute traumatic myelopathy: an acute cervical cord injury in the setting of a stable spine with either congenital and/or degenerative stenosis.